2005
DOI: 10.1103/physrevd.71.077901
|View full text |Cite
|
Sign up to set email alerts
|

Sterile neutrinos in neutrinoless double beta decay

Abstract: We study possible contribution of the Majorana neutrino mass eigenstate ν h dominated by a sterile neutrino component to neutrinoless double beta (0νββ) decay. From the current experimental lower bound on the 0νββ-decay half-life of 76 Ge we derive stringent constraints on the ν h − ν e mixing in a wide region of the values of ν h mass. We discuss cosmological and astrophysical status of ν h in this mass region.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 26 publications
5
118
0
Order By: Relevance
“…We also notice that the non-unitarity of theŨ PMNS (submatrix) is constrained by a number of observations, as discussed in [51,52]. Further constraints on the active-sterile mixings and on the sterile neutrino masses can be inferred from current bounds arising from neutrinoless double beta decays [53]. In the present scenario, the relevant effective neutrino mass is given by [46,54] …”
Section: Constraintsmentioning
confidence: 90%
“…We also notice that the non-unitarity of theŨ PMNS (submatrix) is constrained by a number of observations, as discussed in [51,52]. Further constraints on the active-sterile mixings and on the sterile neutrino masses can be inferred from current bounds arising from neutrinoless double beta decays [53]. In the present scenario, the relevant effective neutrino mass is given by [46,54] …”
Section: Constraintsmentioning
confidence: 90%
“…[23]. Further, the (β − β − ) 0ν decay within the mechanism involving sterile neutrinos has been given by Benes et al [31]. In the following, we present a brief out line of the required theoretical formalism for the clarity in notations used in the present paper.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In Ref. [22], it was shown that the mixing of a light sterile neutrino (mass ≪ 1 eV) with a much heavier sterile neutrino (mass ≫ 1 GeV) would result in observable signals in current ββ decay experiments, as is the case in other interesting alternative scenarios [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of singlet neutrinos with Majorana masses allows for new processes like lepton number violating interactions, among which neutrinoless double beta decay remains the most important one [65]. In our analysis, we evaluate the contributions of the sterile states to the effective mass m ee according to [66,67]; strong bounds on the effective mass have been set by several experiments, among them GERDA [68], EXO-200 [69,70], KamLAND-ZEN [71].…”
Section: Jhep02(2016)083mentioning
confidence: 99%